PEMETAAN GEOLOGI TEKNIK DAN ANALISIS DAYA DUKUNG BATUAN DAN TANAH DI JALAN TOL SEMARANGâSOLO STA 24,5â28 DAN SEKITARNYA, KABUPATEN SEMARANG, JAWA TENGAH - Meriyen Budi S, Putri
The research area is located in coordinates 110° 26' 50.651" BT–110° 29' 1.201" BT and 7° 16' 13.454" LS–7° 14' 42.464" LS and administratively covers two districts, which are Bawen and Tuntang Districts, Semarang Regency, Central Java. The research area has 8,75 km2 mapped for the scale 1: 10.000. The purposes of this research are to determine the engineering geology conditions and to analyze the bearing capacity of rock and soil in the site plan area of Semarang–Solo Highway STA 24,5–28 and surrounding areas. Geomorphology of the research area consists of volcanic hills and volcanic plain with slope around 0–70%. Engineering geology condition of research area can be divided into Clay Silt Unit, Clay Sand Unit, Andesit Lava Unit, and Pyroclastic Breccia Unit. The allowable bearing capacity value of shallow foundation at 0–16 m depth in BW-11a (STA 24.5) borehole is 1.50–10.37 ton/m2, BW-26 (STA 26.3) borehole is 5.73–13.77 ton/m2, and BW-29 (STA 28) borehole is 5.19–13.77 ton/m2. The allowable bearing capacity value of deep foundation at 0–30 m depth in BW-18 (STA 25) borehole is 250.78–574.75 ton and BW-22 (STA 25.2) borehole is 23.56–538.82 ton. Factors that affect the bearing capacity are soil type, soil activity, and engineering properties. The noncohesive soils will give a higher bearing capacity value than cohesive soils. The high soil activity will makes the bearing capacity value become lower because it has active clay minerals. The engineering properties such as cohesion and angle of internal friction have positive correlation with bearing capacity.